Do Corporate Governance Practices In One Jurisdiction Affect Another One? Lessons from the Panama Papers - Bryane Michael; Say-Hak Goo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
To what extent do corporate governance practices in one jurisdiction affect another? In this paper, we look at the way that Hong Kong's and the Mainland's corporate governance practices have co-evolved, along with offshore incorporations from both places. Drawing on empirical illustrations of the data using analytical techniques like differential equations and Fourier Spectral Analysis, we find a strong relationship across time between changes in corporate governance practices in both jurisdictions as well as offshore incorporations. Our data also support the idea of a theory-free equilibrium level of corporate governance (determined by market participants' own behaviour rather than by a theory-laden econometric model). We show that lethargy likely explains the persistence of corporate governance practices in both places, with innovations in one place correlating with innovations in the other. Such work clearly implies that corporate governance improvements in one place can help encourage such improvements in other markets which have not adopted laws aimed at improving corporate governance.
Keywords: G34; N25; M14; 330; Chinese corporate governance; Panama Papers; corporate governance spill-overs; Fourier spectral analysis